(3GdMeGSI hTQMgGs - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Edi QMeI Gddg hQVhGfg eMeO Hf Gdabjg bGd bGd di CHh GdYdGA ETJed eG hVYg MHjH Hf ChS ef CLfGS GdTYQ GdNeSI YTQ Ydi EKfi YTQ LfjSkG hgj GdWhjd hGdeOjO hGdHSjW hGdhGaQ s
(3BNQgG (B:s
(3cCfeG dHjJ Ch GdHjJ afckG abdUJ ef MhGTjg Yf GdShb JeJ GdMeGSI HMeO Gddg hefg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HChdg Jedc HGSe eMeO Hf eMeO Hf eMeO Hf OGhO GdbOSi GdTGaYi hDQN SfI (B989(3g`s
(3heWGdYI HGSe eMeO Hf GdZRi GdeYGaQis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs